Synthesis of 4-cyanoethylated benzoxazines by visible-light-promoted radical oxycyanomethylation of olefinic amides with bromoacetonitrile. Issue 33 (15th August 2019) - Sun, Song; Zhou, Cong; Cheng, Jiang
Graphical abstract: Highlights: Visible-light-promoted reaction of olefinic amides with bromoacetonitrile. Simple bromoacetonitrile used as cyanoalkyl source. The reaction featured with diverse functional group tolerance. Abstract: A facile and efficient protocol for the visible-light-promoted radical oxycyanomethylation of olefinic amides with bromoacetonitrile has been developed, affording a series of 4-cyanoethylated benzoxazine derivatives in moderate to excellent yields. The reaction featured with diverse functional group tolerance and mild reaction conditions.